2021
DOI: 10.1007/s00339-021-05073-9
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining the localized surface plasmon resonance of copper nanoparticles by defective TiO2 thin films

Abstract: The localized surface plasmon resonance (LSPR) of copper nanoparticles (CuNPs) damps quickly in air due to the easy oxidation of copper atoms. Finding ways to retard the oxidation of CuNPs is critical for the applications based on the LSPR of CuNPs. In this paper, we report on a new method to maintaining the LSPR of CuNPs by deposition of CuNPs on TiO 2 thin films in vacuum followed by annealing in nitrogen ambient. The anti-oxidation properties of the CuNPs were improved greatly. In three days, the LSPR inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…LSPR is an optical property of noble metal nanoparticles, but AgNPs [ 31 ] and CuNPs [ 32 ] are easily oxidized by air. AuNPs have been widely used in experiments due to their good structural stability, so in this review, the binding method of gold nanoparticles and optical fibers is mainly explained.…”
Section: Sensing Principle and Combinationmentioning
confidence: 99%
“…LSPR is an optical property of noble metal nanoparticles, but AgNPs [ 31 ] and CuNPs [ 32 ] are easily oxidized by air. AuNPs have been widely used in experiments due to their good structural stability, so in this review, the binding method of gold nanoparticles and optical fibers is mainly explained.…”
Section: Sensing Principle and Combinationmentioning
confidence: 99%
“…Recently, new techniques have been continuously developed. In 2021, our group first reported a technique using defective TiO 2 thin films as electrons donors to prevent the oxidation of CuNPs, 16 but the protection diminished after 72 hours due to electron depletion. In 2022, Chung et al reported a more effective method for electron supply by growing CuNPs on the surface of a [Gd 2 C] 2+ •2e − electrode; 17 good stability was obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, new techniques have been continuously developed. In 2021, our group first reported a technique using defective TiO 2 thin films as electrons donors to prevent the oxidation of CuNPs, 16 but the protection diminished after 72 hours due to electron depletion. In 2022, Chung et al .…”
Section: Introductionmentioning
confidence: 99%